The role of fluid friction in streamer formation and biofilm growth - Cornelius Wittig; Michael Wagner; Romain Vallon; Thomas Crouzier; Wouter van der Wijngaart; Harald Horn; Shervin Bagheri (npj Biofilms and Microbiomes)
Abstract Biofilms constitute one of the most common forms of living matter, playing an increasingly important role in technology, health, and ecology. While it is well established that biofilm growth and morphology are highly dependent on the external flow environment, the precise role of fluid friction has remained elusive. We grew Bacillus subtilis biofilms on flat surfaces of a channel in a laminar flow at wall shear stresses spanning one order of magnitude (τ w  = 0.068 Pa to τ w  = 0.67 Pa). By monitoring the three-dimensional distribution of biofilm over seven days, we found that the biofilms consist of smaller microcolonies, shaped like leaning pillars, many of which feature a streamer in the form of a thin filament that originates near the tip of the pillar. While the shape, size, and distribution of these microcolonies depend on the imposed shear stress, the same structural features appear consistently for all shear stress values. The formation of streamers occurs after the development of a base structure, suggesting that the latter induces a secondary flow that triggers streamer formation. Moreover, we observed that the biofilm volume grows approximately linearly over seven days for all shear stress values, with a growth rate inversely proportional to the wall shear stress. We develop a scaling model, providing insight into the mechanisms by which friction limits biofilm growth.